Tocilizumab binds to canine IL-6 receptor and elicits in-vitro inhibitory biological response - Merbl, Yael; Lopez Baltazar, Jesus M.; Byron, Michael; Chan, Sarah K. C.; Ehrlich, Jacqueline J.; Yu, Qiuming (Frontiers in Veterinary Science, 2025)
IntroductionTocilizumab (TCZ) is an immunosuppressive drug approved for the treatment of rheumatoid arthritis in humans. Molecularly, it is a humanized monoclonal antibody (mAb) that binds to the interleukin-6 receptor (IL-6R), blocking its inflammatory pathway with the IL-6 protein. A previous study has looked at the safety of topical TCZ as eye drops in dogs, however, no studies have tested its potential use in canine diseases based on species antibody differences.Materials and methods(1) To assess the biological inhibitory effect of TCZ on canine macrophages in vitro (n = 3), the median fluorescence intensity of phospho-STAT3 (Y705) was determined using flow cytometry and compared to the inhibitory effect of human macrophages (n = 2). (2) To try and characterize the receptor region of interest in the canine IL-6R, homology modeling was performed using the MODELLER 10.4 software. (3) To investigate the real-time ligand-binding affinity and kinetic parameters for canine IL-6R with TCZ, surface plasmon resonance (SPR) spectroscopy was used, and results were compared to the human IL-6R interaction with TCZ.ResultsOur results confirm binding of TCZ with canine IL-6R. In comparison, canine IL-6R binds two orders of magnitude less than human IL-6R in its dissociation constant. Canine cell culture required a higher concentration of TCZ compared to human cell culture to produce a similar inhibitory effect.Conclusions and clinical significanceThe binding of TCZ to canine IL-6R resulting in a biological response is a specific example of the new possibilities to harness humanized mAb for canine diseases. TCZ may not be a feasible treatment due to the binding affinity and the high concentrations needed. However, future studies should explore potential suitable human mAb for treating canine autoimmune diseases.